Effectiveness of Pedagogical Competence: A Development Model through Association of Biology Teachers’ Forum - Anif, S.; Sutama, S.; Prayitno, H. J.; Idrus, N. B. M. (Jurnal Pendidikan IPA Indonesia, 2019)
The results of teacher competency test performed by the Centre of Human Resource Development on Education and Education Quality Assurance have indicated less effectiveness of a certification program. A regional subject teacher association called MGMP (Musyawarah Guru Mata Pelajaran) board, is also known as a forum of all subject teachers with a strategic role in increasing teachers’ professionalism in carrying out their duties as professional teachers. The main objectives of the study were to describe the mechanism of pedagogical competence development activities for biology teachers in a post-certification program through MGMP forum and to identify the characteristics of the activities of biology MGMP. The research method was of survey type and the data collection instruments were a list of questions, polling, and a questionnaire. The respondents included the head of educational quality assurance agency or LPMP (Lembaga Penjamin Mutu Pendidikan) Central Java, education officers of Surakarta, principals, biology MGMP board, as well as biology teachers, selected through purposive sampling method. The results of this study revealed that the mechanisms and the procedures of activities to develop the pedagogical competence of biology teachers in the post-certification program in Surakarta through MGMP were: MKKS (Musyawarah Kerja Kepala Sekolah) or association of school principles networking initiate coordination with district education office, biology MGMP conducts a gathering to devise programs and activities for a year with guidance from supervisor and MGMP board, MKKS or coordinators of MGMP authorize devised programs and activities, implementation of needs-based activities, determination of resource persons, and evaluation to obtain feedback for programs and activities of subsequent years. Furthermore, characteristics of activities based on the priority were: review of Graduate Competency Standard (GCS); preparation of final exam exercises and national exam try-out, and analysis of previous national exam; preparation of student worksheets, preparation of modules, preparation of lesson plan (LP), comprehension of learning materials, enrichment of laboratory materials; workshop of classroom action research (CAR), and preparation of incidental materials. The outcomes produced by biology teachers after carrying out the activities were: final exam exercise, national exam try-out and GCS, syllabus and lesson plan, learning methods and appraisal instruments, CAR proposal, as well as modules/teaching materials/props. The constraints encountered in the implementation of the activities were: funding issues, unstructured and discontinuous programs, complexity of providing resource persons, absence of guidance and supervision, and lack of teacher’s awareness. Meanwhile, several solutions to overcome the constraints in order to support the effectiveness of the activities were: comprehension of biology learning materials, enrichment of laboratory materials, collaboration with universities, CAR follow-up, more structured and continuous programs and activities, as well as supervision and guidance from supervisors.